Prognostic value of coronary computed tomography angiographic derived fractional flow reserve: a systematic review and meta-analysis. Issue 3 (22nd October 2021) - Nørgaard, Bjarne L; Gaur, Sara; Fairbairn, Timothy A; Douglas, Pam S; Jensen, Jesper M; Patel, Manesh R; Ihdayhid, Abdul R; Ko, Brian S H; Sellers, Stephanie L; Weir-McCall, Jonathan; Matsuo, Hitoshi; Sand, Niels Peter R; et al.
Abstract : Objectives: To obtain more powerful assessment of the prognostic value of fractional flow reserveCT testing we performed a systematic literature review and collaborative meta-analysis of studies that assessed clinical outcomes of CT-derived calculation of FFR (FFRCT ) (HeartFlow) analysis in patients with stable coronary artery disease (CAD). Methods: We searched PubMed and Web of Science electronic databases for published studies that evaluated clinical outcomes following fractional flow reserveCT testing between 1 January 2010 and 31 December 2020. The primary endpoint was defined as 'all-cause mortality (ACM) or myocardial infarction (MI)' at 12-month follow-up. Exploratory analyses were performed using major adverse cardiovascular events (MACEs, ACM+MI+unplanned revascularisation), ACM, MI, spontaneous MI or unplanned (>3 months) revascularisation as the endpoint. Results: Five studies were identified including a total of 5460 patients eligible for meta-analyses. The primary endpoint occurred in 60 (1.1%) patients, 0.6% (13/2126) with FFRCT >0.80% and 1.4% (47/3334) with FFRCT ≤0.80 (relative risk (RR) 2.31 (95% CI 1.29 to 4.13), p=0.005). Likewise, MACE, MI, spontaneous MI or unplanned revascularisation occurred more frequently in patients with FFRCT ≤0.80 versus patients with FFRCT >0.80. Each 0.10-unit FFRCT reduction was associated with a greater risk of the primary endpoint (RR 1.67 (95% CI 1.47 to 1.87), p<0.001). Conclusions: The 12-month outcomes in patients with stable CAD show low rates of events in those with a negative FFRCT result, and lower risk of an unfavourable outcome in patients with a negative test result compared with patients with a positive test result. Moreover, the FFRCT numerical value was inversely associated with outcomes.